Kinematics of the Feline Antebrachiocarpal Joint from Supination to Pronation - Basa, Rachel M.; Parr, William C.H.; Tan, Christopher J.; Walsh, William R.; Johnson, Kenneth A. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective Cats rely on their forelimb mobility for everyday activities including climbing and grooming. Supination and pronation of the forelimb in cats are considered to primarily involve the antebrachium, rather than the carpus. Therefore, our null hypothesis was that there would be no movement of the carpal bones (radial carpal bone, ulnar carpal bone and accessory carpal bone) relative to the ulna during supination and pronation.Study Design Eight feline cadaveric forelimbs were rotated from supination to pronation in a jig and computed tomography was performed in the neutral, supinated and pronated positions. The individual carpal bones were segmented from computed tomography images of the supinated and pronated scans in each of the eight specimens. A feline ulna coordinate system was established and used to quantify the translations and rotations between bones of the proximal carpal row and antebrachium.Results After the carpus was rotated from the initial supinated position into pronation, there was significant translation (x, y and z axes) and rotation (x and y axes) of the proximal row of carpal bones based on absolute magnitude values. Given the differences in translations and rotations of the proximal row of carpal bones, our null hypothesis was rejected.Conclusion The proximal row of carpal bones translate and rotate independently from the ulna in the cat during pronation of the antebrachium. This may have future implications in the diagnosis and management of feline carpal injuries involving the antebrachiocarpal joint.
Keywords: kinematics; feline; antebrachiocarpal joint; carpus; pronation/supination